Unravelling the Battle of Britain Lace Panel. (2nd January 2020) - Quarini, Carol
Abstract: The Battle of Britain commemorative lace panel was made by Dobson & Browne between 1942 and 1946 to commemorate the famous air battle that was a pivotal moment in World War II. It is a huge piece of machine-made lace measuring 180 × 65 inches (450 × 163 cm). This paper considers the collaborative nature of the endeavor and aims to reveal some of the hidden heritage behind the lace. It also considers the myths that have grown up around the production of the panel and shows how these are refuted by the materiality of the lace and the capacity of the lace machines. As well as exploring the genesis and production of the panel, this paper considers a commission for a contemporary textile response to the panel and its associated archive material.